Advanced Design For Manufacturing of Integrated Sustainability “Off-Shore” and “Off-Site” Prototype - MVP “S2_HOME” - Nava Consuelo (Civil Engineering Journal, 2020)
The "S2_Home" research project - double safety home - the double safety of living (seismic and social / environmental), pursues the development and research strategy of the De Masi Mechanical Industries of Antonino De Masi, on the themes of innovation related to technologies of automated mechanics, applied to the realization of systems and components at the service of health and quality of life of users. S2_Home pursues the integrated sustainability model between "off-shore" and "off-site" processes. "Off-site" because it applies solutions inspired by robotic automation and advanced manufacturing for the components of a building system between machine shops and off-site. a laboratory for the assembly of systems and services; "off-shore" because it initiates processes of "energy transition" for small and medium-sized user communities. The design process transfers the housing energy-environmental performance of the standard module to the whole integrated supply system, up to the realization of a superior energetic functional model entrusted to the "smart grid". The S2_Home housing module is realized through mobile and self-mounting living systems, that meet the demand for emergency settlements, focusing on the quality of living, the efficiency of operation and usage, and the versatility of construction for different climates and sites sensitive, to the innovation of technological systems and supplies, that are able to characterize the module and make it available to aggregation settlement systems. To realize the economic value through optimizing energy and service operations, as well as the economy of scale on the production chain, using techniques and processes of the company's machine shops.